The practice of code-switching in THR Raaga broadcasting / Sharmila Sambanthan - Sharmila , Sambanthan (2019)
Code-switching is a common practice in a multilingual and multiracial region like Malaysia, particularly among the Tamil speaking community. It is a type of strategy used by bilingual or multilingual Tamils in their radio communication in which they alternate between two or more languages in a certain conversational context. The study aims to explore the types of code-switching employed by THR Raaga announcers and audiences and the interactional functions for them to code-switch in their radio discourse. The study uses non-participation observation method. Audio recordings that consist of spontaneous speeches of the announcers and audiences are retrieved and transcribed and utilised as instrument in obtaining data required for the study. Findings show that THR Raaga announcers and audiences apply code-switching in their radio interactions, adequately switches from their mother tongue, Tamil to English as the second language. They are reported to employ three types of code-switching while communicating in THR Raaga, namely tag switching, intrasentential and intersentential code-switching. It is also discovered that THR Raaga announcers’ and audiences’ code-switching serve eight functions including referential, expressive, phatic, poetic, habitual experience, solidarity, principle of economy and random switching. The result of this study reveals that code-switching is a tool used to favour an effective communication although it may affect the purity of Tamil language.